2009
DOI: 10.1080/00016350902794818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of improvement in periodontal inflammation by toothbrushing on serum lipopolysaccharide concentration and liver injury in rats

Abstract: Toothbrushing promoted healing of periodontal lesions, decreased serum lipopolysaccharide concentration and suppressed liver injury in a rat periodontitis model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 19 publications
3
31
1
Order By: Relevance
“…It has been reported that GGT blood levels were positively associated with attachment level in alcoholic persons, but not in non-alcoholic persons [24]. On the other hand, there are some reports about a relationship between periodontal diseases and liver disease [25, 26]. The present data appear to support such reports.…”
Section: Discussionsupporting
confidence: 86%
“…It has been reported that GGT blood levels were positively associated with attachment level in alcoholic persons, but not in non-alcoholic persons [24]. On the other hand, there are some reports about a relationship between periodontal diseases and liver disease [25, 26]. The present data appear to support such reports.…”
Section: Discussionsupporting
confidence: 86%
“…Oxidative stress may cause direct damage to cells and tissues, as well as stimulating production of proinflammatory cytokines . Decreasing GSH/GSSG ratio is an indicator of local alterations in gingival redox balance as well as increasing circulating oxidative stress . In this study ligature placement for lower incisors resulted in a decrease trend in the GSH/GSSG ratio (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…In another study, induced‐periodontitis in rats determined oxidative damage of the liver . These observations support the possibility that periodontal disease could promote hepatic oxidative damage by increasing oxidative stress, respectively MDA and reduce GSH …”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations